Gold nanoparticle-based method for detection of calcium carbide in artificially ripened mangoes (Magnifera indica). Issue 6 (3rd June 2018) - Lakade, Ankita Jagannath; Sundar, Kothandapani; Shetty, Prathapkumar Halady
ABSTRACT: A new approach was developed for a simple and easy colorimetric detection assay to detect the use of calcium carbide in artificial ripening of fruits. Residues of arsenic on the fruit surface were used as an indicator for this. Use of calcium carbide in artificial ripening has been banned in many countries including India. In the present study, we have used a gold nanoparticle (AuNP)-based colorimetric detection method for determination of artificial ripening of fruits. ICP-MS analysis showed the presence of higher amounts of arsenic on fruits ripened using calcium carbide. Lauryl sulphate (LS)-capped AuNP aggregates in the presence of arsenic, replacing the LS, resulting in a colour change from red to purple. Hence, the developed method can be used for easy and rapid detection of use of calcium carbide in artificial ripening of fruits. GRAPHICAL ABSTRACT: